Relationships among anthropometric and stroking characteristics of college swimmers - Grimston, S. K.; Hay, J. G. (Medicine & Science in Sports & Exercise, 1986)
Frontal areas, cross-sectional areas, and lengths of body segments were measured on 12 members of the University of Iowa men's swimming team during the Big Ten Championships over two years. Data were gathered through photographic procedures. Stroke length, stroke frequency, and swimming speed were determined from five films of competitive events for each subject. Anthropometric variables were correlated with the three performance variables. Six variables, five of them determined genetically, were significantly related to one or more performance variables. 1. Stroke length was correlated positively with axilla cross-sectional area (.74), arm length (.68), hand cross-sectional area (.57), leg frontal area (.61), and foot cross-sectional area (.68). 2. Stroke frequency was correlated negatively with axilla cross-sectional area XSA (-.73), arm length (-.59), leg length (-.64). 3. Swimming speed was not correlated with any of the variables. Anthropometric variables accounted for 89% of stroke length, 41% of stroke frequency, and 17% of speed variances. The axilla cross-sectional area was shown to have the largest relationship accounting for 54% of the variance in stroke length and 24% in stroke frequency. It was concluded that speed is influenced little by the physique of the swimmer but that stroke length and frequency are. It would seem that bigger swimmers stroke longer at lower rates while smaller swimmers stroke shorter but rate higher. Implications: Successful male swimmers often have been shown to have large feet and hands, and long arms and legs. This study confirms that long-limbed individuals with large hands and feet have a predisposition to success in swimming.